Blockchain-based Notarization for Social Media - Song, Gyuwon; Lee, Kwanhoon; Haejin, Hwang; Kim, Suhyun (2019 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2019)
This paper presents a blockchain-based notarization service for social media. With the advent of smartphones, social media platforms have become an undeniably popular way to communicate with people across the world. However, fake news and maliciously fabricated screenshots are continuously produced and distributed on social media. Since blockchain technology can store data in a secure and tamper-proof way, it is a suitable platform for notarizing online activity. The problem is how we can verify the data to notarize. We propose an architecture that can authentically archive the contents on social media using blockchain technology. Based on the proposed method, an instant messaging scenario is presented as a proof-of-concept.